SPECIALIZED PRODUCTS OF PROBIOTIC USE: QUALITY AND FUNCTIONALITY - Lobach E.Y.; Gur'yanov Y.G.; Poznyakovskiy V.M.; Kostin A.N. (Техника и технология пищевых производств)
Specialized food products including biologically active additives (BAA) are becoming increasingly in demand in the consumer market taking into account their importance for improving people’s nutrition and health. The aim of the research is to develop probiotic confectionery of "Bifidopan" and "Laktopan" enriched with bifidobacteria (bifidobacterium adolescentis), lactobacilli (lactobacillus plantarum and lactobacillus acidophilus) and ascorbic acid in the following amount: bifidogum (1 * 1010 CFU, g / 100g) - 0.5; lactogum (1 * 1010 CFU, g / 100 g) and acidodum (1 * 1010 CFU, g / 100 g) - 0.25. The introduction reflects relevance of our research and the development of dietary supplements. To achieve this goal we used generally accepted and special research methods determined by technical regulations [9]. The article reflects the prescription composition, organoleptic indices, and nutritional value of the developed products. The results of the research on safety indices for candies are given as well as recommendations for doses of their consumption have been developed. We studied organoleptic, physical-chemical, sanitary-hygienic, sanitary and toxicology factors of quality and safety that allowed us to establish nutritional value of the developed products. The mass fraction of ascorbic acid mg / 100 g is 900; bifidobacteria (bifidobacterium adolescentis) (for sweets "Bifidopan") CFU / 100g is at least 5.0 * 109; lactic acid bacteria (lactobacillus plantarum and lactobacillus acidophilus) (for sweets "Laktopan") CFU / 100 g is at least 5.0 * 108; fats g / 100 g (averaged data) is 20.5; carbohydrates g / 100 g (averaged data) is 67.3. The energy value is 454 kcal. These indices as well as the analysis of probiotics participation in the regulation of metabolic processes determine the functional character of specialized confectionery products. Evidence of their effectiveness is provided by including them in the children diet as a comprehensive therapy for chronic gastroenteritis and gastrointestinal diseases. Normalization of intestinal microflora and clinical symptoms of the disease has been established against the background of improving self-awareness and general state of the body. High stability of BAA has been demonstrated by the example of the most labile component - ascorbic acid, which is explained by using gentle production process parameters that provide a slight level of humidity and aeration preventing undesired oxidation processes. Recommendations on the norms of consumption of the developed products are given. Based on the materials obtained, the conclusion on the possibility of using probiotic sweets as a source of functionally active bifido-, lactobacilli and ascorbic acid has been made. Specialized products have been tested under production conditions certified within the requirements of international standards ISO 9001, 22000 series and GMP rules, which ensures the stability of their quality characteristics and competitiveness.